Nitrous Oxide Emission on Cropland Management System in Rainfed Rice Field - M. ARIANI; R. KARTIKAWATI; P. SETYANTO (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2011)
Organic material application for cultivated crops is assumed to be improving the activity of denitrification microbe and N2O emission. Natural N2O emission can increase due to agricultural activity. This activity directly adds the nitrogen input into soil and can be converted into N2O form. The amount of 1,25% N applied into soil as organic manure was transformed into N2O. This research objective is to study the emission of nitrous oxide (N2O) from rainfed ricefield with various crop management system. This research was conducted at Indonesian Agricultural Environment Research Institute (IAERI) in RS 2009 and designed in Randomized Block Design replicated three times with six treatments, ie. (1) Non-Integrated Crop Management (Non ICM)/control ; with anorganic fertilizer as farmer’s suggestion (120 kg ha-1 N, 90 kg ha-1 P, and 90 kg ha-1 K); without organic materials; continuous irrigation (continously flooded), seeds 25 DAS and plant distance 20 x 20 cm. : (2) Non-ICM/Control ; equal to treatment 1 but using the intermittent irrigation; (3) ICM with the continous irrigation, young seed (15 DAS) one seed per hole, fertilization pursuant to schema of leaf colour chart (BWD), organic materials equal to 2 ton / ha, continuous irrigation (continously flooded) and legowo planting system with legowo 2:1 (20-10 cm) x 40 cm. (4) ICM; equal to treatment 3 but using the intermittent irrigation (5) SRI with the intermittent irrigation; organic manure equal to 15 t ha-1, young seed 15 DAS, without anorganic fertilization and plant distance 30 x 30 cm; (6) Semi-SRI, equal to treatment 5 but with half of farmer’s dosage of anorganic fertilizer, with the intermittent irrigation. The result shows that the highest N2O emission yielded by treatment Non ICM equal to 0.23 kg ha-1 season-1 followed by treatment continuously flooded ICM , Non ICM intermitten,SRI intermitten, Semi SRI Intermitten and ICM intermitten 0.22; 0.21; 0.18; 0.13; and 0.10 kg ha-1 season-1 respectively. While, the highest rice yield is gained from treatment Non ICM Intermittent that is equal to 7.99 t ha-1, followed successively treatment of ICM Intermitten, ICM continuously flooded, Non ICM continuously flooded, Semi SRI intermitten and SRI intermitten each of 7.83; 7.42; 7.28; 6.20; and 4.74 t ha-1